2018
DOI: 10.3892/mmr.2018.8867
|View full text |Cite
|
Sign up to set email alerts
|

PEEK‑biphasic bioceramic composites promote mandibular defect repair and upregulate BMP‑2 expression in rabbits

Abstract: The present study aimed to investigate whether bone morphogenetic protein-2 (BMP-2) was involved in the repair of mandibular defects using polyether-ether-ketone biphasic bioceramic (PEEK-BBC) composites in rabbits. PEEK-BBC composites with abundant and interconnected pores were prepared by calcination and characterized by scanning electron microscope. A mandibular defect model in rabbits was established using dental grinder to produce a square hole. A total of 60 rabbits were divided into four groups: Control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Only qualitative data extracted from each study were synthesized in analytic tables. In seven of the 13 included studies, New Zealand rabbits were used [16,[115][116][117][118][119][120], while six studies were conducted in rats, of which three used the Sprague-Dawley strain [17,121,122], two the Wistar strain [123,124] and one the Lewis strain [125]. The calvarial critical-sized defect was the most used model for assessing new bone formation (Table 3).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Only qualitative data extracted from each study were synthesized in analytic tables. In seven of the 13 included studies, New Zealand rabbits were used [16,[115][116][117][118][119][120], while six studies were conducted in rats, of which three used the Sprague-Dawley strain [17,121,122], two the Wistar strain [123,124] and one the Lewis strain [125]. The calvarial critical-sized defect was the most used model for assessing new bone formation (Table 3).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Notably, all the included studies reported uneventful healing outcomes and no relevant adverse reactions. Two studies reported on the use of polyether-ether-ketone/odontogenic biphasic bioceramic composites (PEEK-BBC) prepared via calcination for the treatment of mandibular bone defects [16,115]. Porous PEEK-BBC composites were found to promote bone healing in vivo, potentially via the upregulation of bone morphogenetic protein-2 (BMP-2), as suggested by the higher mRNA and protein expression levels of BMP-2 in the presence of PEEK-BBC composites, than in bone defects left empty [16].…”
Section: Studies In Rabbits-main Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies included with the rabbit model all have the calvaria bone defect. Other research has used other sites such as the mandibular bone [ 38 , 40 ], femoral defect [ 32 ] and radial defect [ 41 ].…”
Section: Discussionmentioning
confidence: 99%